Wastewater reuse in agriculture: the effect of macrophyte-assisted vermifiltration treatment on seed germination and seedling development. Issue 9 (11th August 2022) - Nsiah-Gyambibi, Rapheal; Quashie, Andrews; Armoo, Ekua Afrakoma
Abstract: There is a growing need to reclaim wastewater for agricultural use due to freshwater limitation. Integrating macrophytes in vermifiltration improves the treatment efficiency. However, the effect of treated wastewater on seed germination and seedling development is not widely investigated. The study investigated the use of Pistia stratiotes in a macrophyte-assisted vermifiltration of domestic wastewater and assessed the effect on seed and seedling development of Zea mays, Triticum aestivum and Sorghum bicolor . Three irrigation treatments of water were applied: macrophyte-assisted vermifiltration (VP), no macrophyte vermifiltration (VM) and potable water (PW) as the control. Results showed that VP had a removal of 41–44% EC, 65–67% turbidity, 52–65% TDS, 67–70% TSS, 29–34% COD, 42–46% BOD, 67–70% N total, and 74–78% P available compared to VM. VP treatment reduced inhibition in the morphological, physiological and biochemical developments of seed and seedling growth. The use of macrophyte-vermifiltered wastewater significantly ( p < 0.05) increased the percentage of germination and the radical length of all seed species increased as well. In terms of the seedling development, seedling mortalities were significantly ( p < 0.05) reduced and more than 75% chlorophyll pigments estimations (Cɑ, Cɓ, Cɑ+ɓ and Cx+c ) were identified in all seedling species when macrophyte-vermifiltered wastewater was used to irrigate. HIGHLIGHTS: Vermifiltration of domestic wastewater integrated with macrophytes proved effective. Pistia stratiote was suitable as a macrophyte in the water treatment process. Treated wastewater indicated a potential water source for irrigation. Water treatment reduced inhibition in seed growth and development. Macrophyte-assisted vermifiltration of domestic wastewater revealed a sustainable domestic wastewater treatment technology. Graphical Abstract